Earth-abundant WC nanoparticles as an active noble-metal-free co-catalyst for the highly boosted photocatalytic H2 production over g-C3N4 nanosheets under visible light. Issue 5 (20th February 2017) - He, Kelin; Xie, Jun; Yang, Zhuohong; Shen, Rongchen; Fang, Yueping; Ma, Song; Chen, Xiaobo; Li, Xin
Abstract : Enhanced visible-light photocatalytic H2 evolution over g-C3 N4 nanosheets modified by earth-abundant WC nanoparticles as an active noble-metal-free co-catalyst. Abstract : In an attempt to construct extremely robust photocatalytic H2 -evolution systems, the search for highly active and durable earth-abundant H2 -evolution co-catalysts remains a great challenge. Herein, composite photocatalysts of g-C3 N4 nanosheets and a Pt-like WC co-catalyst was firstly synthesized via a one-step high-temperature calcination strategy. The visible-light-driven photocatalytic hydrogen production performance over g-C3 N4 nanosheets loaded by the earth-abundant tungsten carbide, which act as an active noble-metal-free co-catalyst, was further investigated using TEOA as an electron donor. The results showed that the loading of the WC co-catalyst could significantly boost the photocatalytic performance of g-C3 N4 nanosheets under visible-light irradiation. Moreover, it was demonstrated that g-C3 N4 nanosheets loaded with 15 wt% WC co-catalyst could achieve the highest hydrogen production rate of 146.1 μmol g −1 h −1, which is 1.1 and 56.1 times that of the g-C3 N4 -1 wt% Pt and g-C3 N4 photocatalysts, respectively. The remarkably enhanced hydrogen evolution activities could be ascribed to the loading of abundant WC co-catalyst onto the g-C3 N4 nanosheets, which effectively improves visible-light absorption, promotes the separation of charge carriers, and enhances the subsequent hydrogen evolution kinetics. This study paves a new way for the rational design and development of extremely robust photocatalysts loaded by earth-abundant metal carbides, which can act as noble-metal-free co-catalysts, for the enhancement of H2 evolution activity.